Managing dub with progesterone - locally or orally which is a better option? - Pathak, Anu; Singh, Saroj; Agarwal, Rachana; Verma, Charu; Goyal, Yogesh K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The levonorgestrel intrauterine system (LNG-IUS) is a safe and effective form of contraception used by millions of people worldwide. Other than this, it has many non-contraceptive benefits-treatments for dysfunctional uterine bleeding (DUB), fibroid uterus, endometriosis and endometrial hyperplasia. Methods: A prospective longitudinal comparative study was carried out at department of obstetrics and gynaecology S.N. Medical College, Agra, Uttar Pradesh, India including 100 women of 20-45 years of age group (comparable in all aspects), with DUB. All cases were subjected to detailed history, examination and baseline investigations- Hemoglobin (Hb), endometrial aspiration, histopathology and ultrasound pelvis (along with endometrial thickness) and PBAC scoring before starting the treatment. Then cases were randomly allocated in two equal groups. In group A LNG-IUS was inserted. In group B cases were prescribed oral medroxy progesterone acetate 10 mg bd from 5th and 25th day of menstrual cycle. Cases were followed at 1 month, 3 months and 6 months after starting treatment. At each follow-up visit primary outcome in terms of subjective assessment by patient, PBAC scores and secondary outcome as Hb levels and side-effects were recorded. Results: Reduction in PBAC Scores, improvement in Hb and reduction in endometrial thickness were seen with both treatment modalities but results were significantly (p <0.0001) better with LNG-IUS group as compared to MPA. LNG-IUS was found to be more effective in endometrial hyperplasia and proliferative type of endometrium. Conclusions: LNG-IUS is a good alternative to oral progesterone therapy for patients of DUB.